2023
DOI: 10.1093/jas/skad130
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected finding of Fusobacterium varium as the dominant Fusobacterium species in cattle rumen: potential implications for liver abscess etiology and interventions

Abstract: Fusobacterium varium has been generally overlooked in cattle rumen microbiome studies relative to the presumably more abundant liver abscess-causing Fusobacterium necrophorum. However, F. varium was found to be more abundant in the rumen fluid of cattle and under culture conditions tailored to enrich F. necrophorum. Using near-full length 16S rRNA sequencing, we demonstrate that F. varium grows under restrictive conditions commonly used to enumerate F. necrophorum, suggesting that previous F. necrophorum abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Here, we report the two strains containing the erm(B) gene have dose dependent, growth phase, and preconditioning dependent responses, showing a lack of inhibition at environmentally relevant concentrations and up to 100 μg/mL for FN38. We also ran the same experiments on a strain previously observed to be susceptible to tylosin: 40 ATCC 25286, whose genome was previously sequenced and annotated. 42 FNC, a strain highly susceptible to tylosin, and whose genome we sequenced, was also included.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report the two strains containing the erm(B) gene have dose dependent, growth phase, and preconditioning dependent responses, showing a lack of inhibition at environmentally relevant concentrations and up to 100 μg/mL for FN38. We also ran the same experiments on a strain previously observed to be susceptible to tylosin: 40 ATCC 25286, whose genome was previously sequenced and annotated. 42 FNC, a strain highly susceptible to tylosin, and whose genome we sequenced, was also included.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previously, the tylosin susceptibility of F. necrophorum has been discussed at length, using a range of dosages in both laboratory experiments and in vivo (4 μg/mL, 9.4–16 μg/mL, 10.5–11.5 μg/mL, 12 μg/mL, 45 μg/mL, 90 mg/steer/day). Here, we report the two strains containing the erm (B) gene have dose dependent, growth phase, and preconditioning dependent responses, showing a lack of inhibition at environmentally relevant concentrations and up to 100 μg/mL for FN38.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with our results, Petri et al ( 66 ) found a high abundance of the genera Olsenella and Comamonas in animals with induced ruminal acidosis. The Fusobacterium genus is a normal inhabitant of the rumen of cattle, however, some species from this genus are opportunistic pathogens and primary causative of rumen abscesses ( 67 , 68 ). The presence of this microbial genera in the treated animals highlights the possibility of using microbial taxa as biomarkers for subacute acidosis.…”
Section: Discussionmentioning
confidence: 99%